Case report: Cutaneous anthrax diagnosed using mNGS of a formalin-fixed paraffin-embedded tissue sample - Zhang, Jin; Hou, Xin-Yi; Wang, Jing-Yu; Lu, Bin (Frontiers in Cellular and Infection Microbiology, 2024)
The metagenomic next-generation sequencing (mNGS) method is preferred for genotyping useful for the identification of organisms, illumination of metabolic pathways, and determination of microbiota. It can accurately obtain all the nucleic acid information in the test sample. Anthrax is one of the most important zoonotic diseases, infecting mainly herbivores and occasionally humans. The disease has four typical clinical forms, cutaneous, gastrointestinal, inhalation, and injection, all of which may result in sepsis or meningitis, with cutaneous being the most common form. Here, we report a case of cutaneous anthrax diagnosed by mNGS in a butcher. Histopathology of a skin biopsy revealed PAS-positive bacilli. Formalin-fixed paraffin-embedded (FFPE) tissue sample was confirmed the diagnosis of anthrax by mNGS. He was cured with intravenous penicillin. To our knowledge, this is the first case of cutaneous anthrax diagnosed by mNGS using FFPE tissue. mNGS is useful for identifying pathogens that are difficult to diagnose with conventional methods, and FFPE samples are simple to manage. Compared with traditional bacterial culture, which is difficult to cultivate and takes a long time, mNGS can quickly and accurately help us diagnose anthrax, so that anthrax can be controlled in a timely manner and prevent the outbreak of epidemic events.